RELOKASI HIPOSENTER MENGGUNAKAN METODE MODIFIED JOINT HYPOCENTER DETERMINATION (STUDI KASUS GEMPABUMI LAUT MALUKU TANGGAL 15 NOVEMBER 2019) - Sabonbali, Sisca Cicilya; Taunaumang, Heinrich; Dungus, Ferdy; Zulkifli, Muhammad; Sriyanto, Sesar Prabu Dwi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
In this study, we determined the accurate hypocenter location of November 15, 2019, the Molucca Sea earthquake aftershocks using the Modified Joint Hypocenter Determination (MJHD) method. This method calculated the hypocenter and seismic station correction simultaneously using the seismic wave travel time inversion. The P and S wave arrival time at each station from the BMKG database was used in this study. After relocated, most of the aftershocks hypocenter categorized as shallow and medium depth earthquakes with the range of focal depth between 25-150 km.